Precursor concentration effect on optical properties of carbon dots from Cassava’s peels - Permono Adi Putro; Liszulfah Roza; Isnaeni Isnaeni (Universitas Sebelas Maret, 2018)
Carbon dots (C-dots) are a new type of fluorescent nanoparticles that can be readily synthesized from natural sources, such as cassava’s peels. In this work, C-dots were synthesized from cassava’s peels using low temperature green synthesis based. The Green synthesis techniques were done by using water as a solvent non-chemical and natural sources. The Synthesis was done using various concentrations of precursor from 0.25%, 0.50%, 1.0% and 2.0%. Optical properties of C-dots were characterized using spectrophotometer UV-Vis, photoluminescence (PL) and time resolved photoluminescence (TRPL). The concentration of precursor lead to differences in molecular density and content of preparation thus affecting optical properties. The performance of C-dots optical properties were dominated by the transition of electrons n–π* on structure aromtic C=O which originate from the surface of C-dots. The result of C-dots sample with a concentration of 2.0% precursors has the best emission effiency. This provides the potential for C-dots cassava’s peels in the aqueous solution to be applied as cellular bioimaging and biosensing metal ions and salts.